2018
DOI: 10.14302/issn.2576-6694.jbbs-18-1887
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of Bilateral Alternating Stimulation Tactile Form Technology on the Stress Response

Abstract: The application of bilateral alternating stimulation in tactile (BLAST) form technology, a non-invasive, somatosensory-based method, has been shown to modulate the electrical activity of brain networks that mediate the stress response, resulting in a stress-reducing effect in individuals with high reported levels of anxiety, such as post-traumatic stress disorder (PTSD). In this study, we examined archival data from a heterogeneous group of users (n = 1109) of BLAST technology via Touchpoints, a novel BLAST-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This agrees with previous work which supports a role for bilateral alternating somatosensory information and EMDR in attenuating the stress response and returning stress induced reactions back to baseline. The statistically significant reduction in subjective stress ratings following treatment with BLAST agrees with a previous study by our group showing significant reductions in subjective ratings of both physical and psychological stress following 30 seconds of treatment with BLAST as compared to their baseline[18]. It also supports several studies which have shown a beneficial effect of EMDR-based treatment on patients with high levels of anxiety[13,15,27].…”
supporting
confidence: 90%
“…This agrees with previous work which supports a role for bilateral alternating somatosensory information and EMDR in attenuating the stress response and returning stress induced reactions back to baseline. The statistically significant reduction in subjective stress ratings following treatment with BLAST agrees with a previous study by our group showing significant reductions in subjective ratings of both physical and psychological stress following 30 seconds of treatment with BLAST as compared to their baseline[18]. It also supports several studies which have shown a beneficial effect of EMDR-based treatment on patients with high levels of anxiety[13,15,27].…”
supporting
confidence: 90%
“…Eye movement desentization and reprocessing (EMDR) -as it was mentioned earlier, EMDR is a relatively young mode of psychotherapy with many studies on its usefulness for different health conditions [20], [46], [52]- [54] The theoretical framework for EMDR is Adaptive Information Processing model (AIP). The model assumes that recovering past negative information and processing them to be included This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A Techniques For Stress and Anxiety Reductionmentioning
confidence: 99%
“…What is more, recent studies have shown that VR may redefine psychological treatment by creating an environment which will help patients to cope with experiences that are a source of mental crises [24]. From the review of research using VR in the therapy of mental disorders, it appears that this type of technology may be conducive to alleviating the symptoms of depression and anxiety disor- [19], (c) TouchPoints solution dedicated for kids [20], (d) EMDR KIT: audio, visual, and tactile processing tools [21], (e) EMDR Elite -an application available on the App Store [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such technologies is the TouchPoints wristband produced by Touchpoint Solution™, Scottsdale, AZ, USA [120]. This solution provides emotional monitoring but also claims to relieve stress using stimulating electrical pulses that a patented technology named Bi-lateral alternating stimulation–tactile (BLAST) [121]. Serin et al have reported a significant reduction in the levels of both emotional stress and bodily distress (i.e., 62% and 50%, respectively) after applying BLAST technology suggesting its potential benefits on the stress response by reducing both emotional stress and disturbing body sensations, though their study lacked blinding and could be subject to a placebo effect.…”
Section: Review Of Physiological and Emotional Wearable Monitoringmentioning
confidence: 99%